PEDAMPINGAN PERANCANGAN LABORATORIUM KESEHATAN DAERAH (LABKESDA) KABUPATEN BANJARNEGARA - Yudono, Yohanes Wahyu Dwi; Sulistyawati, Reni; Rustendi, Iwan (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
In building construction management, priority is given to ensuring the creation of buildings that are functional, authentic, balanced, harmonious and in harmony with the environment, as well as being carried out in an orderly manner and with legal certainty in building management. This is stated in Law Number 28 of 2002 concerning Building Construction. Article 7 paragraph (1) states that every building must meet administrative and technical requirements in accordance with the function of the building. Administrative and technical order can be proven by the existence of a Building Permit (IMB) which has now been changed to a Building Permit (PBG) as regulated in Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 16 of 2021. In the PBG process, the Regional Government supervision carries out a consultation process together with the Professional Expert Team (TPA) at each stage until the issuance of the PBG